(untitled) (Comprehensive Journal of Science, 2026)
The city of Al-Ajilat has witnessed rapid urban transformations that have led to the spread of informal urban growth, resulting from the interaction of demographic, economic, and natural factors, in addition to weak urban planning and local governance. This study aims to analyze patterns of informal growth, examine its causes and urban, social, and environmental implications, and assess the role of urban management in regulating urban expansion. The study relied on a descriptive-analytical approach, based on references, previous studies, and official reports. The results indicated that increasing population growth, rising housing costs, availability of land, and shortcomings in urban management contributed to unplanned urban expansion and the emergence of informal neighborhoods lacking infrastructure and basic services, along with imbalances in land use and traffic congestion. The study proposes adopting sustainable urban planning, developing master plans, strengthening local governance capacities, and involving the local community as key strategies to curb informal growth and achieve balanced and sustainable urban development in the city.